PENDAPATAN USAHATANI NANAS MADU DI DESA JANGAN-JANGAN KECAMATAN PUJANANTING KABUPATEN BARRU - Nurlaela, Nurlaela; Amirullah, Amirullah; Ahmad, Ahfandi (Lembaga Penelitian, Pengembangan, Pemberdayaan Potensi Indonesia, 2025)
Honey pineapple plants have been widely cultivated by the people of Barru district and have become the economic foundation of the local community. This research aims to determine the income of honey pineapple farming in Jangan-Jangan Village, Pujananting District, Barru Regency. This research was conducted in Jangan-jangan Village, Pujanting Subdistrict, Barru Regency. The sample in this study were 15 people who cultivate honey pineapple. The data analysis technique used in this research is quantitative descriptive analysis. The results showed that the average income of honey pineapple farming amounted to Rp. 38,460,089/ha, with total costs of Rp. 46,478,911/ha.